The Effect Of Temperature and Drying Time On The Physicochemistry Of Kluthuk Banana Comb Flour (Musa Balbisiana Colla) - wajdi, wafiqi; Ahmad Mundzir Romdhani (TAPE : Jurnal Teknologi Hasil Pertanian, 2025)
The klutuk banana (Musa balbisiana Colla) is a plant that belongs to the Musaceae family and can grow in the wild. The part of the banana plant that is rarely used or even becomes waste is the trunk because its shape and taste are bland This study used different treatments in the drying process, namely P1 (S: 60℃, W: 16 hours), P2 (S: 80℃, W: 13 hours), P3 (S: 90℃, W: 11 hours) and P0 (S: 70℃, W: 15 hours. The purpose of this study was to determine the water content, carbohydrates and gluten content of kluthuk banana stem flour and also to determine the effect of temperature and drying time on the physicochemical properties of kluthuk banana stem flour. The results of the study of the effect of temperature and drying time on the physicochemical properties of kluthuk banana stem flour using the BNJ advanced test obtained P3 temperature of 80 ℃ time of 13 hours is 0.27%, and water content P1 temperature of 60 ℃ time of 16 hours is 0.94%. Carbohydrate content P4 temperature treatment of 90 ℃ time of 11 hours, is 63.52%, carbohydrate content P1 temperature treatment of 60 ℃ time of 16 hours, is 59.23%, and the gluten content P1 emperature treatment of 60 ℃ time of 16 hours is 14.21%, the highest gluten content in P2 with a temperature treatment of 70 ℃ using a temperature of 15 hours, which is 18.42%.